1991
DOI: 10.1177/104420739100200105
|View full text |Cite
|
Sign up to set email alerts
|

Supported Employment in New York State: A Comparison of Benefits and Costs

Abstract: The rapid growth of supported employment programs in the last five years has been accompanied by the strong belief that through such programs many people with severe disabilities would be more satisfied with their lives and receive higher earnings than in sheltered workshops, work activity centers, and adult day care. This paper presents data collected in New York State that test these propositions and compare the benefits with the costs of operating the supported employment program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 6 publications
(9 reference statements)
3
41
1
Order By: Relevance
“…On the other hand, a study by Lam (1986), wherein sheltered employment was compared with SE, indicates that sheltered (i.e., on-site) employment may be more economically efficient when only monetary benefits and costs are considered. Other recent studies on SE by Conley, Rusch, McCaughrin, and Tines (1989), Conley and Noble (1990), and Noble, Conley, Banerjee, and Goodman (1991) also have reported negative economic benefits resulting from SE. In the latter study it was noted that although the SE programs they examined were not cost-effective during the period under study the programs might become cost-effective at some time in the future.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…On the other hand, a study by Lam (1986), wherein sheltered employment was compared with SE, indicates that sheltered (i.e., on-site) employment may be more economically efficient when only monetary benefits and costs are considered. Other recent studies on SE by Conley, Rusch, McCaughrin, and Tines (1989), Conley and Noble (1990), and Noble, Conley, Banerjee, and Goodman (1991) also have reported negative economic benefits resulting from SE. In the latter study it was noted that although the SE programs they examined were not cost-effective during the period under study the programs might become cost-effective at some time in the future.…”
Section: Resultsmentioning
confidence: 90%
“…Since the mid-sixties, benefit-cost analysis also has been used in large-scale evaluations of federal transitional training programs for the economically disadvantaged (e.g., Long, Mallar, & Thornton, 1981) and for persons with disabilities (e.g., Kerachsky, Thornton, Bloomenthal, Maynard, & Stephens, 1985; Kerachsky & Thornton, 1987;Thornton, Dunstan, & Schore, 1990), and in assessing other demonstration projects which have focused on the training and employment of individuals with disabilities (Hill & Wehman, 1983;Schneider, Martin, & Rusch, 1981). More recently, benefit-cost analysis also has been used in the evaluation of SE services for individuals with severe disabilities in comparisons with other employment and rehabilitative activities (e.g., Conley, Rusch, McCaughrin, & Tines, 1989;Hill, Wehman, Kregel, Banks, & Metzler, 1987;Lam, 1986;Naeve, Allen, Harding, & Shea, 1990;Noble & Conley, 1987;Noble, Conley, Banerjee, & Goodman, 1991), and even in one study directly addressing the prospective benefit-cost effects of school-based special education services (Lewis, Bruininks, Thurlow, & McGrew, 1988). Today, almost all state VR agencies, employ some form of benefit-cost analysis for reporting to legislatures and policymakers on the likely efficiency effects resulting from traditional vocational rehabilitation activities.…”
mentioning
confidence: 99%
“…Other studies on supported employment by Conley et a2. (1989), Conley &Noble (1990, and Noble et al (1991) also have reported negative economic benefits resulting from supported employment.…”
Section: Total Earnings (Continuous) Work Hours (Continuous) Integratmentioning
confidence: 91%
“…Nearly all of the available research has explored the costs of supported employment in only one state or a handful of adult service agency. For instance, Wehman et al have explored the costs of supported employment in Virginia [20][21][22]39], Rusch et al in Illinois [18,30,31,35], Nobel et al in New York [32], Lewis et al in Minnesota [28], Cimera in Wisconsin [11][12][13] and so forth. Only Kregel, Wehman, and Banks [23] explored the costs of supported employment throughout multiple (i.e., 8) states.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few had samples larger than 1,000 (cf. [24,31,32,38]). Moreover, the samples used by previous studies have focused mainly on individuals with mental retardation (cf.…”
Section: Introductionmentioning
confidence: 99%